Pengaruh Variasi Densitas Ethylene Vinyl Acetate (EVA) terhadap Kenyamanan Plantar Pressure Pemain Basket - Dadang Mubin; Galih Farhanto; Edi Irwanto (MAN Insan Cendekia Jambi, 2026)
This study aims to analyze the effect of varying Ethylene Vinyl Acetate (EVA) density in basketball shoe midsoles on plantar pressure distribution and subjective comfort. Using a repeated measures design with 20 basketball players, three EVA density variations were tested: low (0.15 g/cm³), medium (0.25 g/cm³), and high (0.35 g/cm³). Plantar pressure data were collected using in-shoe sensors during vertical landing, cutting, and sprinting maneuvers. The results indicated that medium-density EVA provided the most even pressure distribution (205 ±pm 10 kPa at the heel) compared to low density, which caused lateral instability, or high density, which drastically increased peak pressure (245 ±pm 15 kPa). ANOVA analysis confirmed a significant influence of density on foot kinetic variables (p < 0.001). In conclusion, an EVA density of 0.25 g/cm³ is the optimal point for balancing shock absorption and responsive stability to mitigate the risk of injuries such as plantar fasciitis.